Directional telomeric silencing and lack of canonical B1 elements in two silencer Autonomously Replicating Sequences in S. cerevisiae - Chisamore-Robert, Patricia (BioMed Central, 2012)
BACKGROUND: Autonomously Replicating Sequences (ARS) in S. cerevisiae serve as origins of DNA replication or as components of cis-acting silencers, which impose positional repression at the mating type loci and at the telomeres. Both types of ARS can act as replicators or silencers, however it is not clear how these quite diverse functions are executed. It is believed that all ARS contain a core module of an essential ARS Consensus Sequence (ACS) and a non-essential B1 element. RESULTS: We have tested how the B1 elements contribute to the silencer and replicator function of ARS. We report that the ACS-B1 orientation of ARS has a profound effect on the levels of gene silencing at telomeres. We also report that the destruction of the canonical B1 elements in two silencer ARS (ARS317 and ARS319) has no effect on their silencer and replicator activity. CONCLUSIONS: The observed orientation effects on gene silencing suggest that ARSs can act as both proto-silencers and as insulator elements. In addition, the lack of B1 suggests that the ACS-B1 module could be different in silencer and replicator ARS.